A scoping review of literature on adoption and impact of climate smart agricultural technologies by smallholder farmers in Africa - Rurii, Mercy W.; Nzengya Daniel, Muasya (Frontiers in Climate, 2026)
This scoping review aims to map the literature on empirical evidence on CSA technology adoption among smallholder farmers, to identify critical gaps, and propose future research directions, with a focus on outcomes related to productivity, food security, and resilience. Its unique contribution is in methodically uncovering understudied behavioral and gender gaps in Sub-Saharan Africa, demonstrating oversights that undermine equitable and transformative CSA technologies and impact. Using the PRISMA-ScR framework, the review analyzes 54 peer-reviewed empirical studies (published 2013–2025) selected from an initial 598 articles searched in June 2025 across multiple databases. Inclusion criteria prioritized quantitative and mixed-methods studies employing inferential statistics, excluding qualitative-only works and gray literature. Key findings show binary adoption as the dominant outcome variable (52% of studies), followed by adoption intensity (26%) and decision-making factors (11%). Geographically, research clusters in Ethiopia, Kenya, and Ghana, with scant attention to countries like Tanzania, DRC, Senegal, and Mali. Theoretically, adoption and diffusion models prevail (57.5%), while behavioral (22.5%) and economic frameworks (10%) are underrepresented. Contextually, studies emphasize crop-based practices, largely overlooking livestock systems, gender dynamics, agroecological diversity, and dis-adoption processes. Behavioral factors—such as risk perceptions and environmental attitudes—and gender intersectionality, including intra-household power imbalances, remain underexplored. Methodologically, cross-sectional designs dominate, constraining causal inference and generalizability. Climate change intensifies vulnerabilities for SSA smallholder farmers, where rainfed systems heighten exposure to erratic weather, yield losses, and threats to food systems and livelihoods. CSA emerges as a vital strategy to bolster productivity, resilience, and sustainability, aligning with SDG 13 on climate action. By addressing these evidentiary gaps, the review advocates for inclusive, longitudinal research that links adoption to tangible outcomes like yield stability and income resilience, ultimately informing policies to realize CSA's potential for equitable smallholder farming amid escalating climate extremes.